Awareness, Access, and Use of NDLI and N-LIST E-Resources: A Literature-Based Comparative Study - Yette, Avinash Gajananrao; Manikpure, Rajendra R. (Unisia, 2025)
Digital e-resources significantly enhance academic quality, research and learning in higher education institutions of the country. Two state-owned online resources, namely, the National Digital Library of India (NDLI) and INFLIBNET’s N-LIST, help learners and faculty to access learning resources, which is prevalent reflects in the National Assessment and Accreditation Council (NAAC) evaluation criteria for higher education colleges. This paper develops a literature-based comparative study of NDLI and NLIST both its awareness, accessibility, strengths and limitations, and its relevance with NAAC- accredited institutions within the Vidarbha region of Maharashtra. The papers draw comparative insights from peer-reviewed studies, official documents and reports about these resources. Analyses suggested that both digital e-resources are complementary to each other in nature to promote, NDLI being noted for its open access and multi-lingual free resource content and wider coverage of educational resources, and N-LIST with free access to premium learning resources by subscription. Both sectors also report significant challenges in infrastructures, behaviours suggesting low awareness and use in poorly represented colleges in N-LIST, and daily use of them at universities and colleges. The paper closes with recommendations for institutional research in Vidarbha regarding implementation of digital e-resources and or awareness and training programs and processes aligned to NAAC evaluation criteria, so all online resources are maximized to their benefit.